Bio‐inspired Development of a Dual‐Mode Nanoprobe for MRI and Raman Imaging. Issue 1 (16th September 2014) - Ju, Kuk‐Youn; Lee, Sangyeop; Pyo, Jung; Choo, Jaebum; Lee, Jin‐Kyu
<x xml:space="preserve">Abstract</x> New generation dual‐mode imaging probes for MRI and Raman imaging techniques are developed, inspired by the hyper intense contrast enhancing capability in T1‐weighted MRI and characteristic Raman signal of natural melanin. MDA‐MB‐231cells labeled with dual‐mode imaging probe are successfully detected in both T1‐weighted MRI and Raman imaging. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>